The impact of source water quality on the cost of nitrate treatment. Issue 1 (20th November 2018) - Vedachalam, Sridhar; Mandelia, Ankita J.; Heath, Eric A.
Abstract : Rising nitrate levels in source waters threaten to increase the cost of delivering safe drinking water in many communities. This is especially true in the agriculture‐heavy Mississippi River Basin. This study analyzed water quality and treatment cost data over 10 years at three water utilities in the basin. In each intake watershed, farm fertilizer was the largest contributor of nitrogen loading. Nitrate concentrations generally increased during the study period, resulting in increased intake exceedances above 10 mg/L. The amortized capital cost of the treatment plant typically outweighed annual operation and maintenance (O&M) costs. Furthermore, a scale effect was observed with regard to capital costs—unit cost decreased with an increase in production. Limited data on O&M costs suggest that high‐intake nitrate levels contributed to higher treatment costs. This article discusses the policy implications of the findings and presents recommendations to mitigate ratepayer impacts from high nitrate levels.